2015
DOI: 10.1111/all.12805
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic variation in TLR8 in relation to allergic rhinitis

Abstract: Rare variants in TLR8 are not associated with AR. Comparison of present and previous association studies reveals contradictory results for common variants. Thus, no associations exist between genetic variation in TLR8 and AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…These SNPs are all located in the same haploblock and reflects the association observed earlier for the TLR7 - TLR8 region [ 16 ]. However, no signs of any accumulation of rare variants was detected in TLR8 which was also demonstrated in a previous study [ 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…These SNPs are all located in the same haploblock and reflects the association observed earlier for the TLR7 - TLR8 region [ 16 ]. However, no signs of any accumulation of rare variants was detected in TLR8 which was also demonstrated in a previous study [ 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…A number of studies have established the association of AR with other cytokines and genes such as IL-6 (Zhao et al, 2016); IL-10 and TGF-β polymorphisms (Nasiri et al, 2016); IL-12B (Wei et al, 2016); IL33/IL1RL1, IL-13-RAD50 and C11orf30/LRRC32 (Li et al, 2015); JAK1 gene polymorphisms (Shen et al, 2016). In contrast, Henmyr et al (2016) found no associations between the genetic variation in TLR8 and AR. Moreover, a study on a North Indian population showed that the IL-18 -137G/C polymorphism conferred a significant protection from asthma.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, the duodenal mucosa shows no inflammatory activity despite comparable profile expression of the same TLR genes. This study adds to the cumulative literature investigating the role of TLRs in different gastrointestinal inflammatory conditions, including inflammatory bowel disease 29 , 45 , 46 , celiac disease 30 , 47 , food allergy 48 , and several atopic disorders 49 , 50 .…”
Section: Discussionmentioning
confidence: 97%